A Case Study on Factors Influencing Knowledge Sharing Among Employees in Royal Malaysian Police (RMP), Selangor Contingent Headquarters, Malaysia - Taib, Khairul Mizan; Kadir, Mohd. Razilan Abdul; Yasin, Siti Munira; Yunus, Mohd. Alwi; Shahibi, Mohd. Sazili; Jakaria, Mukram (Journal of Informatics and Mathematical Sciences, 2017)
Knowledge Sharing (KS) is an activity in which knowledge consists of information, skills or expertise possessed by an individual is shared among colleagues in the organization. As the organization is involved with a large number of employees that come from different backgrounds, it is very important for the Royal Malaysian Police (RMP) to standardize or to implement KS activities within the organization. With respect to this, a study was conducted to examine the relationships between KS and daily activities in RMPthrough five main factors: organizational culture, communication, management support, trust, and technology. A survey was conducted randomly among 265 respondents from RMP employees at Selangor Contingent Headquarters. Data analysis was performed to examine the correlation of the factors influencing KS. Results revealed that all of the five factors influencing KS were found to be significantly associated with daily activities in RMP Selangor Contingent Headquarters.